THE SIGNIFICANCE OF BILINGUAL DICTIONARIES IN TEACHING ENGLISH AT SCHOOL, LYCEUM, COLLEGE AND HIGHER EDUCATIONAL ESTABLISHMENTS - Ruzimov, Sh. (SCIENCE and SOCIETY, 2018)
In the article compiling principles of English-Uzbek and Uzbek-English dictionaries were critically investigated and there were given practical recommendations for improving their role in teaching English at schools, lyceums, colleges and higher educational establishments.
Keywords: лексикография; жалб қилмоқ; маънодош; урғу; тамойиллар; танқидий; таклифлар; ишлаб чиқмоқ; яҳлит тизим; илмий